2013
DOI: 10.3109/10717544.2013.823330
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-sensitive mucoadhesive polymer-based dental patches to treat periodontal diseases: anin vitrostudy

Abstract: Local drug delivery for periodontal diseases is still a challenge due to very short residence time, involuntary swallowing and salivary wash-out. Present study is, therefore, an attempt to develop pressure-sensitive adhesive polymers-based mucoadhesive dental patches to ensure satisfactory prolonged release of drugs, to treat periodontal diseases locally. Polymers such as duro-tak Õ 387-2516 and duro-tak Õ 387, ethylcellulose, polyvinylpyrrolidone, polyvinyl alcohol along with drugs amoxicillin trihydrate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Amounts of drug release of FP1 and FP2 in SLF at different time points were found to be generally more (except a few cases where the values were marginally less) than those in PBS at the respective time points. The R 2 values and rate constants/release exponent values determined from the data of drug release following different kinetic models 26 are given in Table 2. More linearity (by assessing R 2 values) was detected in the Korsmeyer−Peppas plot (R 2 = 0.970, 0.921 for FP1, FP2, respectively) followed by Higuchi's (R 2 = 0.952, 0.928 for FP1, FP2, respectively) in SLF.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
“…Amounts of drug release of FP1 and FP2 in SLF at different time points were found to be generally more (except a few cases where the values were marginally less) than those in PBS at the respective time points. The R 2 values and rate constants/release exponent values determined from the data of drug release following different kinetic models 26 are given in Table 2. More linearity (by assessing R 2 values) was detected in the Korsmeyer−Peppas plot (R 2 = 0.970, 0.921 for FP1, FP2, respectively) followed by Higuchi's (R 2 = 0.952, 0.928 for FP1, FP2, respectively) in SLF.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
“…In a different study, Manasadeepa et al [102] reported about formulating and characterizing an innovative dental patch with efficient mucoadhesive properties and pressure sensitiveness. Polymers with confirmed biocompatibility, biodegradability and non-toxicity were chosen for developing this type of formulation.…”
Section: J)mentioning
confidence: 99%
“…The cross-linked PVP hydrogels have been representatively used as adhesives that can be readily adhered to wet biological tissues. 20,21 The inclusion of PCL fibers in the core along with the adhesive PVP parts in the exterior sheaths was necessary to overcome the PVP's lack of mechanical strength. Most importantly, the proposed tissue adhesives were spontaneously composed of multiple fibrous layers, which were formed via salt-induced electrospinning.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A building-block portion, poly­(ε-caprolactone) (PCL; core), with an adhesive material, poly­(vinylpyrrolidone) (PVP; sheath), were successfully merged by coaxial-electrospinning of the dual materials (i.e., PCL@PVP matrices). The cross-linked PVP hydrogels have been representatively used as adhesives that can be readily adhered to wet biological tissues. , The inclusion of PCL fibers in the core along with the adhesive PVP parts in the exterior sheaths was necessary to overcome the PVP’s lack of mechanical strength. Most importantly, the proposed tissue adhesives were spontaneously composed of multiple fibrous layers, which were formed via salt-induced electrospinning .…”
Section: Introductionmentioning
confidence: 99%